'This is why I'm doing a lot of exercise' — a qualitative study of participant's experiences of the Sophia Step Study. Issue 2 (2nd September 2017) - Rossen, Jenny; Lööf, Helena; Yngve, Agneta; Hagströmer, Maria; Brismar, Kerstin; Johansson, Unn-Britt
Abstract : Introduction: Support for physical activity (PA) is central in diabetes care. The Sophia Step Study is a three-armed randomised controlled trial aiming to evaluate different levels of support for increased PA in prediabetes and Type 2 diabetes. With the purpose to reveal the programme components and the mediating factors from the participants' perspective this paper aims to report a qualitative exploration of adhering participants' experiences after two years' study participation. Methods: Semi-structured interviews were conducted with 18 participants (men, n = 11, women, n = 7, prediabetes, n = 5, Type 2 diabetes, n = 13, median age 68.5 years) who completed a two-year multi-component ( n = 7), single-component ( n = 6) intervention or served as controls ( n = 5) at a primary care center in Stockholm, Sweden. The interviews were analysed using content analysis with an inductive approach. Sophia Step Study is registered at ClinicalTrials.gov with Identifier: NCT02374788 . Results: The participants recalled the frequent study assessments as providing feedback of health outcomes; positive reinforcement; a sense of sentinel and a personalised approach. Group meetings, pedometers and health check-ups were valued as resources for increased awareness and motivation of PA; establishment of new routines and control over the own health. The long program duration allowed for maintenance of awareness and routines for PA Conclusion: Adhering participants in theory-based interventions, but also in the control group, identified key mediators to support for PA. Feedback of results, personalised encouragement, emotional support and self-monitoring should be regarded in self-management of PA to optimise patient motivation and outcomes.